Suspected resistance of MDT-MB in Multibacillary Leprosy of Hansen's disease: Two case reports - Irawan, Yudo; Menaldi, Sri Linuwih; SD, Emmy Soedarmi; Marissa, Melani; Zoulba, Erika (UI Scholars Hub, 2016)
Resistance to multidrug therapy (MDT) is one of the complications in the treatment of Hansen’s disease/Morbus Hansen (MH). There are two types of resistancy, which are primary and secondary. MDT-multibacillary (MB) resistance must be suspected when no clinical improvement and the acid-fast bacilli (AFB) index is not reduced after 12 months of therapy. A 28-year-old woman with paresthesia on her face, arms and legs since 2.5 years ago, accompanied by thickening of the right posterior tibial nerve. The AFB examination showed a bacteriological index (BI) of 15/6 and morphological index (MI) of 0.50%. The second case, a 42-year-old man came with paresthetic lesions on his face, chest, back, both arms and legs since 2 years ago, accompanied by thickening of ulnar and lateral peroneal nerve. The BI was 12/5 and the MI was 0.40%. Both patients were diagnosed with borderline lepromatous type of MH and received MDT-MB for 12 months. Diagnosis of suspected resistance was established because no clinical improvement or any significant decrease of AFB index after completing the MDT treatment. The patients had secondary resistance after polymerase chain reaction evaluation showed that they were still rifampicin-sensitive. There was clinical improvement and significant decrease in FAB index after the patients continued the MDT-MB treatment with 600 mg additional rifampicin. The diagnosis of bacterial resistance should be made based on clinical evaluation before completion of treatment. Based on the two case reports, the resistance suspected may be secondary. Treatment using additional regimen can be initiated once the resistance has been proven.